PERGESERAN LEGITIMASI WACANA YURISPRUDENSI ISLAM DALAM SISTEM TATA KELOLA GLOBAL PERSPEKTIF SEJARAH PERADABAN ISLAM - Buro, Hasan HA (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2018)
Islamic jurisprudence gives an example of exceeding legal science generally which is separate from historical considerations, it is the will of God which is declared precedent and not preceded, controlled and not controlled. In its stipulation, Muslim scholars agreed on five sources of Islamic jurisprudence: the Qur'an, Sunna, Ijma, qiyas, and ijtihad. There is almost no idea of ??law itself which develops as a historical phenomenon that is closely related to the progress of society. Naturally the discovery and formulation of divine law is a process of growth, which is systematically divided by traditional doctrine into several different stages. This paper aims to describe the shifting legitimacy of Sharia discourse in the global governance system of the perspective of the history of Islamic Civilization. From the results of the discussion concluded: 1) Islamic jurisprudence has undergone many historical changes since the time of the Prophet Muhammad, and researchers have divided their development into several historical stages. The role of individual jurists is measured by pure subjective standards of the intrinsic value of the process of discovering divine orders. This is not considered to be based on external criteria or in relation to the circumstances of a particular era or region. 2) tracing the origins of the basic elements of Islamic law has the same problem by tracing the origins of the Qur'an itself, and many scholars are satisfied to only associate the origins of Islamic law with the concern of Muslims to apply the Koran. If Al-Quran comes from seventh-century Arabic, then some basic elements of Islamic law also come from there. If the Qur'an was canonized to change the Arab conquest, then it reflected the early formative period of Islamic law rather than its formation. 3) some media authorities try to change the legal legal doctrine that seeks more than just reforming Islamic law. However, this problem cannot be applied until the last decade of modern law being implemented because the power of traditional Islamic attitudes is still relevant to modern law with its implications, therefore the source of Islamic heritage cannot be compared to dehistorizing Islam.